Time course of changes in bone resorption markers during pamidronate therapy in breast cancer patients with bone metastases - A. D. Petrova; M. B. Stenina; L. V. Manzyuk; N. V. Lyubimova; S. A. Tyulyandin (Опухоли женской репродуктивной системы)
The paper gives the results of evaluating the time course of changes in the level of bone resorption markers (S-CTx and dPir) in pami- dronate-treated patients with bone metastases from breast cancer. It shows the relationship of these markers to clinical and X-ray find- ings. The markers were not found to be of high clinical significance as a means for diagnosing bone metastases and estimating treat- ment trends.